Perancangan Interaksi dan Antarmuka Pengguna Sistem Informasi Pelayanan Jasa Laundry menggunakan Pendekatan Human Centered Design - Agityarizky Tidoputra Pradana; Hanifah Muslimah Az-Zahra; Niken Hendrakusma Wardanai (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
A service definitely requires a system that can help in running its business. Therefore, every business person can develop their business by using the system in it. D'Coin laundry is a coin laundry service company that was only established in mid-2021. In running his business already using the system that is available for free in the application store. But the use of such systems is still not fully used and focuses on manual recording because it is not in accordance with the wants and needs. Therefore, the purpose of this study is to design a system to handle the process of laundry services at D'Coin laundry, which can meet the needs, and provide a good experience for its users. This research uses a Human centered design (HCD) approach. The results of this study are in the form of prototype designs and evaluated with usability testing techniques. After the evaluation, the value of the effectiveness aspect was 100% in 3 respondents and 86% in 1 respondent. The results of the efficiency aspect in the owner respondent group were 100% and in the employee respondent group it was 89.8%. Then for the satisfaction aspect there are 3 problems. After that, prototype repairs were carried out in accordance with problems in the satisfaction aspect.